Percepción de los profesores sobre influencia de la planificación organización dirección y control en el desempeño directivo en instituciones educativas públicas de Capelo Requena 2024 - Oliveira Quintana, Abner (2025)
The research aimed to explain the influence of planning, organization, direction, and control on the managerial performance of public educational institutions in Capelo, Requena Province, during the year 2024. The study involved a sample of 120 teachers from six educational institutions, applying a quantitative, explanatory, correlational, non-experimental, and cross-sectional methodology. Data were collected through surveys and processed with SPSS version 26, using descriptive and inferential statistics. The results showed that although most teachers perceived that management functions were applied only occasionally, no significant correlations were found between these dimensions and the principal’s performance. For example, planning obtained a correlation of -0.050, and direction -0.008, both lacking statistical significance. These findings revealed a disconnect between formal management processes and how school leadership is perceived. It was concluded that managerial performance is not being determined solely by administrative functions, suggesting the need to integrate qualitative dimensions such as commitment, empathetic communication, and close pedagogical support. Consequently, recommendations are proposed for the UGEL, school principals, and teachers, outlining feasible actions to strengthen a more human, coherent, and sustained approach to school management.